Effects of build orientation and heat treatments on the tensile and fracture toughness properties of additively manufactured AlSi10Mg - Araújo, Luana C.; Gabriel, André H.G.; da Fonseca, Eduardo B.; Avila, Julian A. [UNESP]; Jardini, André L.; Seno Junior, Roberto; Lopes, Éder S.N. (Elsevier, 2022)
The purpose of this study aimed to examine how build orientation and heat treatments affect microstructure, and consequently, the mechanical properties obtained from tensile and fracture toughness tests of additively manufactured AlSi10Mg samples. Samples were manufactured in several orientations using a laser-based powder bed fusion (L-PBF) additive manufacturing (AM) process, following which they were subjected to three separate heat treatments: (i) stress relief at 300 °C for 2 h (SR); (ii) homogenization at 540 °C for 2 h followed by artificial aging at 170 °C for 8 h (HA-1); (iii) homogenization at 540 °C for 6 h followed by artificial aging at 170 °C for 14 h (HA-2). Tensile tests showed that the AB samples presented the highest mechanical strength; however, low ductility was also observed. Therefore, a model for crack propagation during tensile testing was proposed for L-PBF typical microstructure. Samples subjected to fracture toughness tests showed sensitivity to porosity and microstructure. The crack-tip opening displacement (CTOD) of the AB and HA-2 samples showed similar average values of approximately 10 µm in all three orientations. The SR samples showed the best fracture toughness behavior with average values ranging from 19 µm to 32 µm. The HA-1 samples presented average values between 13 µm and 22 µm. The fracture toughness values reported in the J-integral ranged from 6.0 to 8.4 kJ.m−2, 10.4 to 15.5 kJ.m−2, 5.5 to 7.8 kJ.m−2, and 4.6 to 5.7 kJ.m−2, respectively, for the AB, SR, HA-1, and HA-2 heat treatments.
Keywords: Aging; anisotropy; CTOD; ductility; J-Integral; porosity